Ar-Rahnu an alternative to conventional pawnshop, challenges and prospect in the future / Nurliyana Ahmad Ghazali - Ahmad Ghazali, Nurliyana (Faculty of Business and Management, 2011)
This research is designed because believed that product called Ar-Rahnu able to be marketed in every country if certain actions can be taken. The demand of the Ar-Rahnu is highly demanded because they believed on the service and know the advantage of the product. The significant of the research is to expose readers and the future researchers that pawnshop is not second class business. Those who know the advantage of Islamic pawnshop will appreciate the system and grab the opportunities that exist in the system. Although pawnshop is a traditional business, new approach can be implemented. With the right marketing approach we believed that Islamic pawnshop can be one the best fund providers. This paper explores the challenges and prospect of Ar-Rahnu besides investigate the factors that influence customers to choose Ar-Rahnu in Malaysia. Besides that this paper also study the challenges faces by Ar-Rahnu which is to know why there are still have people go to conventional pawnshop and the prospect in the future.